1980
DOI: 10.1111/j.1476-5381.1980.tb07031.x
|View full text |Cite
|
Sign up to set email alerts
|

Sites of Action of Mojave Toxin Isolated From the Venom of the Mojave Rattlesnake

Abstract: 1 Mojave toxin isolated from the venom of the Mojave rattlesnake (Crotalus scutulatus scutulatus) produced an irreversible blockade of the contractile response of the mouse hemidiaphragm to stimulation of the phrenic nerve in vitro, at concentrations of 0.16 to 20 pig/ml; the response to direct stimulation was not affected over a testing period of several hours.2 Mojave toxin (1 to 4 ptg/g) was injected into the tail vein of mice and the intoxicated hemidiaphragm preparation was removed either for testing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(18 citation statements)
references
References 27 publications
(41 reference statements)
0
18
0
Order By: Relevance
“…Myonecrosis may be due to the vascular degeneration and ischemia caused by SVMPs, or it may result from the direct action of myotoxins (enzymatic/non-enzymatic) on the plasma membrane of muscle cells. Extensive muscle tissue damage results in weakness of muscle and painful restriction of movements with muscle tenderness [43][44][45][46][47][48][49][50].…”
Section: Local Toxicitymentioning
confidence: 99%
“…Myonecrosis may be due to the vascular degeneration and ischemia caused by SVMPs, or it may result from the direct action of myotoxins (enzymatic/non-enzymatic) on the plasma membrane of muscle cells. Extensive muscle tissue damage results in weakness of muscle and painful restriction of movements with muscle tenderness [43][44][45][46][47][48][49][50].…”
Section: Local Toxicitymentioning
confidence: 99%
“…One study of mice injected with a premixed solution of CroFab TM and C. durissus terrificus venom showed a significant survival benefit compared to mice injected with venom alone [7]. These findings of structural similarity and apparent neutralization in an animal model provided a scientific basis for the use of CroFab™, which contains antibodies to Mojave toxin, to treat envenomation by the South American rattlesnake [6]. Based upon these results, it was felt that CroFab™ administration was appropriate in the absence of more specific antivenom.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a literature search to determine potential effectiveness of its administration for the treatment of this envenomation was performed. Crotoxin, a neurotoxic phospholipase A 2 found in C. durissus terrificus venom, is similar both in molecular weight and toxic effect to Mojave toxin, a component of Mojave rattlesnake (C. sculatus scutulatus) venom [1,6]. Antiserum raised against crotoxin has been shown to neutralize Mojave toxin.…”
Section: Discussionmentioning
confidence: 99%
“…For example, various authors have identified populations of C. scutulatus in central Arizona that do not express Mojave toxin (Glenn and Straight, 1978;Glenn et al, 1983;Wilkinson et al, 1991). Mojave toxin is a presynaptically acting neurotoxin (Gopalakrishnakone et al, 1980) that is composed of two peptides (Aird et al, 1985;Zepeda et al, 1985), a nontoxic acidic subunit (subunit A) and a phospholipase A 2 (PLA 2 ) basic subunit (subunit B), which is mildly toxic (Cate and Bieber, 1978). Both subunits must be present to produce Mojave toxin, which can increase the venom toxicity 10 to 30 times (Tu et al, 1982).…”
mentioning
confidence: 97%